Self-tuning hybrid fuzzy sliding surface control for pneumatic servo system positioning - Mohd Iskandar Putra, Azahar; Addie Irawan, Hashim; Raja Mohd Taufika, Raja Ismail (Elsevier Ltd, 2021)
This paper presents a new robust control strategy developed for the pneumatic servo system (PSS) by hybridizing two types of fuzzy logic control (FLC) rules as a self-tuner to the integral sliding mode control (ISMC), namely self-tuning hybrid fuzzy sliding surface control (SH-FSSC) controller. A sliding surface consisting of two switched fuzzification rules, relying on the tuning threshold value of the position error tracking, was designed to consider both the position and the force feedback of the pneumatic proportional valve with a double-acting cylinder (PPVDC) system. The approach is to acquire multiple features not only on tracking error but also faster transient response with finite-time convergence, chatter elimination, and robustness against uncertainty. The proposed control strategy was verified and validated by conducting experiments with the actual PPVDC unit linked to the tip of the robot’s tri-finger pneumatic grippers (TPG) platform. The experimental works were accomplished using two types of input trajectories: multi-steps and sinusoidal input trajectories. On the other hand, an additional external payload as a disturbance to the test rig has also been added at the end of the pneumatic gripper jaw, intended to evaluate the proposed controller’s robustness performance. The advantage of the proposed method was validated by significantly eliminating oscillation for each transient response, maintaining high tracking performance, and minimizing hysteresis effects. The oscillation was suppressed with minimal overshoot, and the proposed method was achieved without a significant loss of performance.